CoQ10 in progressive supranuclear palsy: A randomized, placebo-controlled, double-blind trial. Issue 5 (October 2016) - Apetauerova, Diana; Scala, Stephanie A.; Hamill, Robert W.; Simon, David K.; Pathak, Subash; Ruthazer, Robin; Standaert, David G.; Yacoubian, Talene A.
Abstract : Objective: An investigator-initiated, multicenter, randomized, placebo-controlled, double-blind clinical trial to determine whether coenzyme Q10 (CoQ10) is safe, well tolerated, and effective in slowing functional decline in progressive supranuclear palsy (PSP). Methods: Sixty-one participants received CoQ10 (2, 400 mg/d) or placebo for up to 12 months. Progressive Supranuclear Palsy Rating Scale (PSPRS), Unified Parkinson's Disease Rating Scale, activities of daily living, Mini-Mental State Examination, the 39-item Parkinson's Disease Questionnaire, and 36-item Short Form Health Survey were monitored at baseline and months 3, 6, 9, and 12. The safety profile of CoQ10 was determined by adverse events, vital signs, and clinical laboratory values. Primary outcome measures were changes in PSPRS and Unified Parkinson's Disease Rating Scale scores from baseline to month 12. Results: CoQ10 was well tolerated. No statistically significant differences were noted between CoQ10 and placebo groups in primary or secondary outcome measures. A nonsignificant difference toward slower clinical decline in the CoQ10 group was observed in total PSPRS among those participants who completed the trial. Before the final study visit at 12 months, 41% of participants withdrew because of travel distance, lack of perceived benefit, comorbidities, or caregiver issues. Conclusions: High doses of CoQ10 did not significantly improve PSP symptoms or disease progression. The high withdrawal rate emphasizes the difficulty of conducting clinical trials in patients with PSP. ClinicalTrials.gov identifier: NCT00382824. Classification of evidence: This study provides Class II evidence that CoQ10 does not significantly slow functional decline in PSP. The study lacks the precision to exclude a moderate benefit of CoQ10.